The Нigher Education of Turkey and Bologna Process - V. A. Avatkov (MGIMO University Press, 2012)
The article analyses the complex of issues connected with the system of higher education in Turkey. It emphasizes the facts how it was integrated into Bologna system. There are also the prospects of the system given and analyzed. What is more, the article draws analogies with Russia and scrutinizes them.